Preparação de membranas poliméricas porosas a partir de técnicas de espumação com agentes físicos de expansão - Almeida, Ronaldo José de (Universidade Federal de São Carlos, 2016)
The objective of this master’s thesis was to develop a process of manufacturing porous polymer membranes for microfiltration by a one-step foaming technique, using carbon dioxide (CO2) as physical blowing agent and ethanol (etOH) as co-solvent. Initially this work was conducted with PC/PMMA polymer blend samples in hollow fiber geometry, varying the blend composition, foaming temperature and the co-solvent content. It was determined that the blend composition PC/PMMA 60/40, sorbed with CO2 at 40°C with an ethanol content of 10%mol (CO2 molar basis) provided an opened porous morphology with potential for filtering applications. However, the pronounced fiber wall expansion ratio after the foaming process resulted in a considerable reduction of the fibers inner diameter, hindering its application as a hollow fiber membrane. Thus, it was necessary to change the hollow fiber geometry for flat films. DSC analysis showed that the PC/PMMA is a partially miscible blend. Gravimetric sorption tests revealed a higher sorption of diluents in polymers after adding ethanol as co-solvent with CO2, resulted from a stronger affinity between the polymers and the CO2/etOH mixture. Gas permeation tests showed a maximum pore size smaller than 10 micrometers, which is considered as an upper limit in the definition of microfiltration membranes. However, when compared to commercial membranes, the samples showed a considerably lower water permeation. With respect to the samples morphology, SEM images of the flat film samples revealed a cross section formed by a porous central region with micrometric interconnected pores, while the skin layers were composed of dense and foamed regions.
Keywords: Membranas poliméricas porosas; Microfiltração; Espumação de polímeros; Agentes físicos de expansão; Dióxido de carbono supercrítico; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS